Quantifying the Effect of Temperature, Pressure, and Depth on Methane Adsorption in Shale Gas Reservoirs for Longmaxi Shale in Sichuan Basin, China - Imbula, Nadeg; Sayed , Iqbal Muhammad (IJRDO-Journal of Applied Science, 2021)
Shale gas is an important unconventional energy source and plays an important role in oil and gas exploration. A significant portion of gas in the shale gas reservoir exists in an adsorbed state. Thus, knowledge of gas adsorption behavior is important. The purpose of this study was to analyze the Longmaxi shale gas adsorption in the Sichuan basin in China. Data have been analyzed by using Multiple regressions, the Langmuir model. The methane adsorption isotherms on shale were tested at 25°C, 40°C and 50°C with the pressure. A total of three shale samples with rock properties as total organic carbon (TOC), Illite- Smectite (I / S) clay minerals, and specific area of the Sichuan basin were analyzed to quantify the effect of temperature on methane adsorption in shale gas reservoirs and study the effect of sample properties on the adsorption. The results showed that the isothermal adsorption methane increase with TOC, but temperature and depth have a negative influence on the gas adsorption. We also conclude that clay minerals and area have a positive correlation with Langmuir volume. All data for the methane adsorption isotherms were adjusted with the Langmuir equation.